Immunohistochemical Expression of Epidermal Growth Factor Receptors (EGF-R) on Normal and Different Kind of Tumoral Adult Lung Tissues - Take, Gülnur; Ilgaz, Celal; Özoğul, Candan; Erdoğan, Deniz; Dursun, Ayşe (Fırat University, 2002)
Aim: In this study it is aimed to investigate immunohistochemical expression of Epidermal Growth Factor Receptors (EGF-R) on normal and different kind of tumoral adult lung tissues Methods: Immunohistochemical methods and polyclonal antibodies used to demonstrate the EGF receptor (EGF-R) localization in normal, non-small cell epidermoid carsinoma and small cell carsinoma adult lung tissues. The results were comparatively analyzed on light microscope. Results: We found that no immunoreactivity was present in small cell carcinoma. But mild immunoreactivity was detected in bronchiolus epithelium of normal lung tissues. On the other hand weak immunoreactivity was seen in apical cytoplasm of bronchiolus epithelium in neigbouring areas of tumoral tissue in epidermoid carcinoma but strong reactivity was recognized in all cancer cells of tumoral places. Wheras weak cytoplasmic reactivity was seen in type I alveolar cells of normal adult lung tissues, there was mild reactivity in type II alveolar cells. Moreover type I and type II olveolar cells reactivity was changing from mild to weak in neigbouring tumoral tissues. Conclusion: These results were shown that EGF-R is effective in the formation of carcinogenesis of some type of tumours.

Amaç: Bu çalışmada normal erişkin akciğer dokusu ile az differansiye epidermoid karsinom ve küçük hücreli karsinom örneklerinde EGF reseptörlerinin dağılımının incelenmesi amaçlanmıştır. Gereç ve Yöntem: İmmunohistokimyasal yöntemle poliklonal EGF-R antikoru kullanılarak EGF reseptörlerinin dağılımları karşılaştırmalı olarak ışık mikroskobu düzeyinde değerlendirilmiştir. Bulgular: Küçük hücreli karsinomda immünreaktivite gözlenmedi. Normal akciğer dokusu bronkiyolus epitelinde reaktivite yalnızca apikal sitoplazmada orta dereceli olarak belirlendi. Bunun yanında epidermoid karsinomda tümöre komşu alanda bronkiyolus epitelindeki tutulum zayıf olarak belirlendi. Tümör alanında tümoral hücrelerin genelinde yoğun ve diffüz membranöz immün boyanma saptandı. Normal erişkin akciğer dokusu alveollerinde tip I alveolar hücrelerde zayıf dereceli, tip II alveolar hücrelerde ise orta dereceli immünreaktivite gözlenirken tümöre komşu alanda tip I ve tip II alveolar hücre reaktivitesinin orta dereceden zayıfa değişkenlik gösterdiği dikkati çekti. Sonuç: Sonuç olarak bu bulgular EGF-R'nin bazı tümör tiplerinin karsinogenezisinde etkili olabileceğini düşündürmüştür.
Erişkinlerde Normal ve Çeşitli Tümöral Akciğer Dokularında Epidermal Büyüme Faktör Reseptörlerinin (Egf-R) İmmünohistokimyasal Olarak Gösterilmesi